How Do Combined Pharmacological And Psychotherapeutic Interventions Impact Treatment Outcomes For Patients With Treatment- Resistant Major Depressive Disorder? : A Systematic Review - Julisman Itolo Dwijaya Daeli; Andy Soemara (The International Journal of Medical Science and Health Research, 2025)
Introduction: Treatment-resistant major depressive disorder (TRD), characterized by an inadequate response to at least two antidepressant trials, presents a significant clinical challenge. Combined pharmacological and psychotherapeutic interventions have emerged as a promising strategy, potentially offering synergistic benefits over monotherapy by addressing both biological and psychological aspects of the disorder. This review synthesizes evidence on the efficacy, mechanisms, and clinical applicability of combined interventions for TRD. Methods: This systematic review followed PRISMA 2020 guidelines. Studies were included if they focused on adult patients with TRD, examined combined pharmacotherapy and psychotherapy, were randomized controlled trials (RCTs), systematic reviews, or meta-analyses, included quantitative depression measures, and had an intervention duration of at least 8 weeks. Searches were conducted in PubMed, Semantic Scholar, Sagepub, and Google Scholar. Results: Forty studies were included, comprising 20 RCTs and 19 systematic reviews/meta-analyses. Combined interventions generally demonstrated superior response and remission rates compared to monotherapy. For instance, one study found response rates of 30.3% for mindfulness-based cognitive therapy (MBCT) plus treatment as usual versus 15.3% for controls. Meta-analyses reported moderate effect sizes (Cohen’s d = 0.32–0.93) and risk ratios of 1.25–1.27 favoring combination therapy. Discussion: The findings underscore the superior efficacy of combined pharmacological and psychotherapeutic interventions for TRD. These approaches lead to significant improvements in response and remission rates, particularly in severe or chronic TRD. Conclusion: The evidence strongly supports combined pharmacological and psychotherapeutic interventions as the gold standard for TRD, offering enhanced efficacy, reduced relapse rates, and good tolerability. Future research should continue to optimize sequencing, explore novel adjuncts, and improve accessibility through digital platforms.